1992
DOI: 10.1042/bj2880511
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of S-adenosylmethionine decarboxylase activity by alterations in the intracellular polyamine content

Abstract: The effects of addition of exogenous spermidine and spermine and of two inhibitors of polyamine biosynthesis, alpha-difluoromethylornithine (DFMO), which decreases spermidine concentrations, and n-butyl-1,3-diaminopropane, which depletes spermine, on the expression of S-adenosylmethionine decarboxylase (AdoMetDC) activity were studied in mammalian cell lines (HT29, CHO and COS-7). AdoMetDC levels were inversely related to the polyamine content, and spermine was the more potent repressor of AdoMetDC activity, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
59
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 37 publications
(41 reference statements)
9
59
0
Order By: Relevance
“…The PEST sequence has been reported to be located in some proteins with fast turnover rates and be essential for the interaction between SCF complex and target proteins, which consequently leads to ubiquitination/26S proteasome-mediated degradation (Kiernan et al, 2001;Berset et al, 2002;Blondel et al, 2005;Pal et al, 2007). Human SAMDC was reported to have a short half-life and is regulated at multiple levels, such as the transcriptional, translational, and posttranslational levels (Shantz et al, 1992;Stanley et al, 1994;Hanfrey et al, 2003;Yerlikaya and Stanley, 2004). Taking all the information above together, we wanted to ask whether the interaction with BSCTV C2 can affect with the stability of SAMDC1.…”
Section: Bsctv C2 Interacts With Arabidopsis Samdc1mentioning
confidence: 99%
See 2 more Smart Citations
“…The PEST sequence has been reported to be located in some proteins with fast turnover rates and be essential for the interaction between SCF complex and target proteins, which consequently leads to ubiquitination/26S proteasome-mediated degradation (Kiernan et al, 2001;Berset et al, 2002;Blondel et al, 2005;Pal et al, 2007). Human SAMDC was reported to have a short half-life and is regulated at multiple levels, such as the transcriptional, translational, and posttranslational levels (Shantz et al, 1992;Stanley et al, 1994;Hanfrey et al, 2003;Yerlikaya and Stanley, 2004). Taking all the information above together, we wanted to ask whether the interaction with BSCTV C2 can affect with the stability of SAMDC1.…”
Section: Bsctv C2 Interacts With Arabidopsis Samdc1mentioning
confidence: 99%
“…Our results of the wheat germ and Arabidopsis cell-free assays also indicated that Arabidopsis SAMDC1 is degraded in a similar 26S proteasome-dependent manner. Cellular activity of SAMDC is reported to be regulated at multiple levels, such as transcriptional, translational, and posttranslational (Shirahata and Pegg, 1986;Kameji and Pegg, 1987;Pegg, 1988;Pegg et al, 1988;Stanley et al, 1989;Shantz et al, 1992), one of which is likely mediated by a cellular protein degradation system. Our wheat germ and Arabidopsis cell-free assay data suggested that BSCTV C2 may positively regulate SAMDC1 at a posttranslational level.…”
Section: Bsctv C2 Positively Regulates Samdc1mentioning
confidence: 99%
See 1 more Smart Citation
“…The mature catalytically active enzyme consists of a dimer (␣ 2 ␤ 2 ) of these subunits (5). Cellular AdoMetDC activity is tightly regulated at multiple levels: transcription of the AdoMetDC gene is repressed by spermidine, the translation of its mRNA is negatively regulated by spermine (6), and the processing of the proenzyme and the catalytic activity of the final enzyme are stimulated by the spermidine precursor putrescine (7,8). It has been reported that the half-life of AdoMetDC is inversely related to the cellular content of spermidine and spermine (9 -11), so that when the levels of polyamines are high, increased degradation of AdoMetDC serves as another important control mechanism in maintaining AdoMetDC activity and therefore polyamine levels (3,5).…”
mentioning
confidence: 99%
“…4). ODC activities, or due to a deficit in the activities for spermine synthesis, the intracellular concentrations of dcSAM increase (Frostesjo et al, 1997;Pegg et al, 2011;Shantz et al, 1992;Yamamoto et al, 2010). Simultaneously, such cells have been reported to have enhanced demethylation status of the entire genome (Papazafiri & Osborne, 1987;Tsuji et al, 2001).…”
Section: The Relationship Between Polyamines and Gene Methylationmentioning
confidence: 99%